THE STUDENTS' ABILITY AND PROBLEMS IN WRITING A RESEARCH PROPOSAL - Widiastuti, Sri (2010)
This study aims to investigate the students' ability and problems in writing a research proposal. This study used a case study method, particularly text analysis. The participants of this study were nine students and two lecturers of an undergraduate English study program in one university in Banten. This study employed two data collection techniques, i.e. the documentation of students' research proposals and interview. The data were, then, analyzed based on the theory of genre analysis and SFL, and validated by triangulation and member checks. The study reveals three findings related to the research questions. First, despite their ability in the discourse semantic level, most students still have problems in achieving the communicative purpose of each major element in a research proposal. Second, the main causes of the problems are the students' unfamiliarity and lack of knowledge in terms of the elements and linguistic features required in a research proposal. Finally, the solutions that can be proposed to solve the students' problems are guidance, assistance, and explicit teaching for the students in writing the elements and linguistic features of a research proposal. It is thus recommended that all the subjects related to writing and research should allow students to have the capacity needed in writing a research proposal.